SYNTHESIS OF THE MANNOSIDASE INHIBITORS SWAINSONINE AND 1,4-DIDEOXY-1,4-IMINO-D-MANNITOL AND OF THE RING CONTRACTED SWAINSONINES, (1S, 2R, 7R, 7AR)-1,2,7-TRIHYDROXYPYRROLIZIDINE AND (1S, 2R, 7S, 7AR)-1,2,7-TRIHYDROXYPYRROLIZIDINE - Carpenter, N; Fleet, G; Dibello, I; Winchester, B; Fellows, L; Nash, R (1989)
4,5-Anhydro-1-azido-1-deoxy-2,3-O-isopropylidene-D-talitol is a divergent intermediate for the efficient and practical syntheses of 1,4-dideoxy-1,4-imino-D-mannitol, swainsonine and of the ring contracted swainsonines, (1S, 2R, 7R, 7aR)-1,2,7-trihydroxypyrrolizidine and (1S, 2R, 7S, 7aR)-1,2,7-trihydroxypyrrolizidine. The effect on glycosidases of the ring contracted swainsonines is reported. © 1989.